2009
DOI: 10.1590/s1984-46702009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Explaining dissimilarities in macroinvertebrate assemblages among stream sites using environmental variables

Abstract: ABSTRACT. The relationship between community structure and environmental factors usually varies according to ecosystem type, group of organisms, and spatial scale. In this study I assessed whether dissimilarities among assemblages of stream macroinvertebrates are related to differences in environmental variables. Data consisted of macroinvertebrate samples of 10 stream sites during the dry season. Seven environmental variables were assessed. The relationship among dissimilarities in assemblage structure and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
3
23
0
1
Order By: Relevance
“…However, only the electrical conductivity significantly correlated with abundance, as found in previous works on first order streams, indicating the importance of this parameter as the structuring of macroinvertebrates assemblages (Baptista et al, 2001;Melo, 2009).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, only the electrical conductivity significantly correlated with abundance, as found in previous works on first order streams, indicating the importance of this parameter as the structuring of macroinvertebrates assemblages (Baptista et al, 2001;Melo, 2009).…”
Section: Discussionsupporting
confidence: 78%
“…The macroinvertebrate community may differ according to structural variables (substrate composition, food availability and flow velocity) in a small scale or can result of water limnological differences in a large scale (Kikuchi and Uieda, 1998;Melo, 2009). Moreover, abiotic variables may be divided in macro or meso spatial scale in which mesoscale can be structural and limnological with hierarchical relationship between these scales influencing organisms (Vilella et al, 2004;Kubíková et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between the structure of biological communities and environmental factors have been found in many studies in aquatic environments (e.g. ; Melo, 2009;Haig-They et al, 2010), some of which were addressed to the phytoplankton community (e.g. Calijuri et al, 2002;Borges et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Some Brazilian studies has shown how water quality variables can influence the entomofauna. Melo (2009) found distinctly different macroinvertebrate communities in nearby sites (streams) in Southeastern Brazil and concluded that these were a result of different levels of conductivity and stream size (orders). Futhermore, Roque et al (2010) analyzed the Chironomidae fauna from 61 streams and discussed the importance of both local (conductivity) and broad (riparian forest cover) scales on the aquatic community composition in streams of São Paulo State.…”
Section: Chironomidae Faunamentioning
confidence: 99%